Strike Settlement and Economic Activity : An Empirical Analysis - Swidinsky, R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
This paper explores the relationship between the outcome of strike and the level of economic activity. The findings are based on Canadian data for the period 1901-1953.